(untitled) (Journal of Parents and Teachers, 2015)
Summary: In a simple way we give eight guidance to help children in situations of death: time, not only words but gestures and presence, concrete attention, helping to accept the character of irreversibility, taking into account their age, honestly answering their questions and never overprotect